Pemanfaatan Media Internet sebagai Sumber Belajar dalam Implementasi Kurikulum 2013 di SD N 3 Donorojo Sempor Kebumen - Jamroh Jamroh; Sigit Mangun Wardoyo; Siti Julaeha (Jurnal Kependidikan, 2021)
The purpose of this study is to analyze the use of Internet media as a learning resource by students and teachers in learning. This study uses a qualitative research approach with the type of phenomenological research. Data were collected by observation, interviews, and documentation. Then analyzed using three stages, namely data reduction, data presentation, and verification. The results of this study indicate that students are familiar with Internet media from various sources including social media, parents and television. As for the use of Internet media facilities by students, including Google, YouTube, and learning applications as learning resources. Students in the use of Internet media have the skills to access various information that is used to support learning resources. Meanwhile, the use of Internet media by teachers is at the planning stage which includes socializing online learning procedures, preparing online Learning Implementation Plans (RPP), downloading applications that will be used in e-learning, and downloading materials. The implementation phase includes the use of Internet media to optimize applications used in e-learning, as well as the use of Google and YouTube as learning resources. The learning outcomes stage includes the use of Internet media to evaluate, guide, and send assignments online.